Participation of the sultanate of ternate in the unitary state of Indonesia - Rusdi Hasan, Oktosiyanti MT. Abd Rustam Hasim (Opción, 2019)
This paper aims to reconstruct the political participation of Sultanate of Ternate in the Unitary State of Republic of Indonesia after independence in 1945. The method used in this paper is a historical method, namely heuristics, criticism, interpretation, and historiography. As a result, the State of East Indonesia (Negara Indonesia Timur or NIT) was formed and covered Sulawesi region, the Lesser Sunda (Bali and Nusa Tenggara) and Moluccas Islands. In conclusion, peace, justice, and prosperity, are the keywords that how important the nobility is, in the eyes of the people.